An Analytical Study of Hadiths on Family Maintenance - Subandi, Ayyub (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
This study regarding living in the household has been narrated through several hadiths, one of which is the hadith of Aisyah ra. about the story of questions Hindun bintu ’Utbah ra. to the Prophet. about the maintenance of his family. This hadith is a proposal in the nafaqat chapter, where the scholars make it a guide in many matters of living and other than that, advise it, and make legal istinbat from it in the books of hadith and fiqh such as providing for a family in its primary needs is the husband’s obligation, where the size returns to urf habit and if a husband is negligent from the obligation to provide for his family, then it is permissible for a wife to take her husband’s property without his knowledge, but only as needed for herself and her child.